The battle on the digital trading floor a review of the securities regulation code vis-a-vis information-based manipulation of securities through the internet (2021)
Market manipulation has become rampant since the Internet boom around 40 years ago. The continuous evolution of technology in financial and digital industnes has given rise to new ways for manipulators to scheme and prey on innocent investors. In light of these innovations, the 20-year-old Securities Regulation Code must be revisited to update policy directions and regulations and combat misinformation online. Regulators should wage the war against information-based manipulation with the help of publicly listed companies, one of the key participants in the capital market. This Article reviews the Code's provisions, specifically on information- based manipulation, and assesses whether these provisions are still effective against the evolving digital schemes. The author argues that there is a need to obligate publicly listed companies to disavow misinformation online and to impose on Internet personalities strict standards when sharing information with the general public. Publicly listed companies should register their verified social media accounts with regulators and post statements denouncing false or misleading statements circulating online. Intemet personalities must also comply with such requirements while emphasizing to their followers the need to countercheck and verify any information before making any investment decisions.
Keywords: Market manipulation; Security management